Biofertilizer formulation comprising phosphate solubilizing bacteria to enhance phosphate availability for cocoa growth - Abd Samad, Mohd Yusoff (2012)
Production of cocoa can be enhanced by good fertilizer application which normally using inorganic fertilizers. However, prolonged use of inorganic fertilizers poses many environmental problems. The use of microorganisms as biofertilizer with specific functional abilities in the mobilization of nutrients is an alternative to mineral fertilizer for enhancement of soil fertility and crop production in sustainable agriculture. The general objectives of this study were to screen phosphate-solubilizing bacteria (PSB), to formulate the formulation of the bacteria inoculants using cocoa wastes and to study the shelf life of the formulations. Screening of all bacterial isolates from various sources of agricultural soils and wastes were carried out. Twenty-two isolates showed the capability of solubilizing insoluble phosphate by both plate assay and liquid medium techniques. The top three PSB namely Pseudomonas aeruginosa strain AGKT1, Serratia marcescens strain AGKT4 and Bacillus amyloliquefaciens were chosen for subsequent studies. In preparation of seed culture for use in dry and liquid formulations, optimum concentrations of carbon source, nitrogen source, and density of inoculum were determined using response surface methodology. Carrier materials from cocoa pod husk and cocoa bean shell were found to be superiors as organic carrier-based materials for the selected PSB as compared to peat moss. The shelf life of bioinoculants in the dry and liquid formulations was found to be good as they had a high number of viable cells for up to 6 months with the cfu above 5 log10 cfu/g when stored at both temperatures of 10 oC and 28 oC. Application of the dry and liquid formulations on cocoa seedlings showed the good responses to the growth, biomass and chlorophyll content of cocoa seedlings. All the dry formulations significantly increased (P<0.05) fresh and dry plant biomass as well as vegetative growth of cocoa seedlings. The three formulations using cocoa bean shell with Pseudomonas aeruginosa strain AGKT1, Serratia marcescens strain AGKT4 and Bacillus amyloliquefaciens resulted in an increase of 86.74%, 114.31%, and 84.35% of total fresh weight of cocoa seedlings, respectively. The dry matter weight of cocoa seedlings also significantly increased at 30.05%, 48.90%, and 19.69% in the formulation using cocoa bean shell with these three PSB as compared to the control. Enhancement of nutrient uptake by the cocoa seedlings and the increase in nutrients in the soil, in particular to phosphorus (P) availability (> 15 ppm) by most dry formulations indicated that the formulations were superiors as bioinoculant preparation.